The Influence of Employee Competence, Work Environment, Information Technology and Work Motivation on Archive Management - Ticha Nurda Fitri; Syamsir Syamsir (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This research is motivated by the storage of archives that are not all in place, and there is still a build-up of archives next to the table or under the table. No special care is taken of the archives that are stored only when there is a rearrangement of the room, and the archives will be cleaned sober. This research was conducted with the aim of 1) Analyzing the influence of employee competence on Records Management; 2) Analyzing the influence of the work environment on Records Management; 3) Analyzing the influence of information technology on Records Management; 4) Analyzing the effect of work motivation on Records Management; 5) Analyze the effect of employee competence on employee work motivation; 6) Analyze the influence of the environment on employee work motivation; 7) Analyze the influence of information technology on employee work motivation. The population is employees of the Ministry of Religious Affairs of Kerinci Regency, with 43 respondents with saturated sampling techniques. The data analysis technique used in this study is quantitative analysis. The data collected in this study were taken from two sources, namely primary and secondary data. Hypothesis testing in this study was carried out by path analysis. Based on the results of the analysis and discussion, it is known that: 1) Employee competence has a significant effect on Archives Management; 2) Work environment has a significant effect on Archive Management; 3) Information technology has a significant effect on Archives Management; 4) Work automation has a significant effect on Archives Management; significant to Records Management; 5) Employee competence has a significant effect on employee work motivation; 6) Environment has a significant effect on employee work motivation; 7) Information technology has a significant effect on employee work motivation.